Optimization of Belleville Spring by Inspecting Parameter Impacts - Mehmet Onur Genç; Alper Karaduman (International Journal of Automotive Science and Technology, 2019)
Clutch disc transmits the torque by frictional forces from the engine to transmission. For this purpose, clutch disc includes some components such a Belleville spring to provide vibration dampening. Belleville springs are used in order to perform hysteresis function of disc assembly by creating frictional torque into clutch system. Hysteresis function of disc is needed to absorb oscillations and prevent noise issues. Belleville spring geometrical shape is critically important and it defines load characteristic. A load of Belleville spring mainly depends on dimensions of inner diameter, outer diameter, thickness, angle, and slot dimensions. This study investigates the single and multi-objective optimization methodology in the automotive clutch system design. This novel methodology presents the design development approach to powertrain system components.